Analysis Of Non-Performing Loan (Npl) Loans Impact Coronavirus Disease 2019 (Covid-19) Case Study At Pt. Banten Regional Development Bank, Tbk Cilegon Branch Office - Siti Kadikah; Dian Febrianti (Lembaga Penelitian dan Pengabdian kepada Masyarakat Politeknik Piksi Input Serang, 2023)
Purpose - The purpose of this paper was to find out how the impact of covid-19 on NPL loans and how Bank Banten Cilegon's efforts in carrying out restructuring/relaxing NPL loans in the covid-19 pandemic situation. Design/methodology/approach - The method used in this research is a qualitative descriptive research method. The technique used in data collection where the source of the data obtained is primary and secondary data. Finding - PT. The Banten Regional Development Bank, Tbk Cilegon Branch Office implements a credit restructuring/ relaxing policy for customers affected by covid-19 in accordance with the policies stipulated by POJK Number 11/POJK.03/2020. In addition, PT. The Banten Regional Development Bank, Tbk Cilegon Branch Office also applies the precautionary principle. This aims to minimize the risk of non-performing loans that can occur at any time. The impact of covid-19 on NPL credit has a major impact on bank health and bank liquidity. Originality - From the results of the discussion, with the covid-19 PT. The Banten Regional Development Bank, Tbk Cilegon Branch Office rescued credit, namely by carrying out credit restructuring/relaxation for debtors affected by the covid-19 pandemic in accordance with the policies stipulated by POJK Number 11/POJK.03/2020 by providing leniency in paying arrears. Both arrears of principal, interest and extending the installment period. However, if the NPL credit had previously experienced a loss before the covid-19 pandemic, the bank could not process restructuring /loan relaxation